- Every Subsequent method for integer factorization is based on Simpler Observation based on Legender's Congruence introduced By Adrien-Marle legender (1752 - 1833)
proof :
-
if we want factorization number n which is composed of factor p,q ϵ P ( set of all prime number ) There exist congruence of form
≡
mod n and y ≠ x mod n Where x,y ϵ ( 2 , 3 , ..... n - 1 )
-
This Congruence can Be Written as
≡ ( X - Y ) ( X + Y ) ≡ 0 mod n which lead us to that p | (x - y) (x + y) and q | (x-y)(x+y) because of condition and x ≠ y mod n .
-
There are only two option for each Condition .
-
First Condition consider if p | (x - y)(x + y) is chosen .
-
Then We have that p | (x - y) and p * x (x + y) or p * x (x - y) and p | (x + y)
-
but if p | (x - y) and p | (x + y)
-
∴ n | (x - y) or n | (x + y)
-
∴ (x - y = k1 * n) or (x + y = k2 * n)
-
∴ x = y + k1 * n or x = k2 * n - y
-
∴ x ≡ y mod n or x ≡ -y mod n which is contradict with our condition
-
∴ p | (x - y) and px (x + y) or px (x - y) and p | (x + y)
-
at the first case if p | (x - y) and px (x + y) we must have that qx (x - y) if q | (x - y)
-
we will have n | (x - y) → x ≡ y mod n ( contradiction )
-
∴ q*x (x - y) but q | (x + y)(x - y) , q ϵ P
-
∴ q | (x - y) ∴ gcd( x - y , n) = p , gcd( x + y , n) = q
-
at the second case if p*x (x - y) and p | (x + y)
-
we must have that q*x (x + y) or if q | (x + y) → n | (x + y) → x ≡ -y mod n (contradiction)
-
∴ qx (x - y) but q | (x + y)(x - y) , q ϵ P
-
∴ q | (x - y) ∴ gcd(x-y , n) = p , gcd(x+y , n) = q
-
In order word if we can get x and y such that
≡
mod n and X ≠±Y mod n
-
then we can calculate easily the value of gcd( x+ y , n) By The Euclidean Algorithm Which is usable for this Purpose , so the principle of factorization based on legender's congruence is behind all modern method of factorization .
End of proof :